Local Peacemaking in South Sudan: PeaceRep Workshop Report - Rob, Wilson (PeaceRep, Coventry University CTPSR, 2024)
This report sets out the discussion points and key insights from a workshop on Local Peacemaking in South Sudan, organised and co-hosted by PeaceRep and the South Sudan Ministry of Peace Building in Juba on 12 October 2023. The workshop brought together 23 local peacebuilders, peace and conflict organisations and researchers working directly in conflict-affected places and on local peace processes in South Sudan. Participants reflected on ways of defining a local agreement, what local agreements should set out to do, and why local agreements matter in relation to the wider conflict context. Discussion focused on themes including local ownership and views of peace processes, how national politics and national or international actors could undermine local peacebuilding efforts, local mediation approaches, inter-ethnic dimensions of local peacebuilding, and community autonomy and self-governance.
Keywords: South Sudan; Peace processes